Instability and Control of Massively Separated Flows:Proceedings of the International Conference on Instability and Control of Massively Separated Flows, held in Prato, Italy, from 4-6 September 2013 - Theofilis, Vassilis (Springer, 2015)
This book contains the outcome of the international meeting on instability, control and noise generated by massive flow separation that was organized at the Monash Center, in Prato, Italy, September 4-6, 2013.